DIATOMEAS DE UNA MUESTRA DE TURBA DE LA FORMACION LOS ALAMITOS ENTRE LOS RIOS DIAMANTE Y MENDOZA, PROVINCIA DE MENDOZA (Ameghiniana, 2013)
Seventeen taxa of diatoms from a peat collected in the Arroyo Yaucha between the Diamante and Mendoza rivers are recorded. They include 12 species, 4 varieties and 1 new form: Stauroneis cbilensis f. pampeana n. f. They suggest a brackish water habitat. The assemblage confirm a postglacial and actual age as stated by Polanski (1962).